The power of shared vision: bidirectional knowledge transfer between expatriates and host country nationals - Ismail, Maimunah; Zulkifly, Nurul Afiqah; Hamzah, Siti Raba'ah (Universiti Malaysia Sarawak, 2019)
Expatriation leads to many organizational outcomes to a host country including knowledge transfer. Little is known about the influence of individual and social capital factors on knowledge transfer involving expatriates and host country nationals (HCNs) bi-directionally. This paper examines the determinants of knowledge transfer involving the two groups of professionals bi-directionally. Focusing on the individual and social capital factors, we investigated the role played by shared vision in the effects of cultural intelligence and feedback-seeking behaviour on knowledge transfer. This empirical study is supported by three theories, namely the resource-based theory, the social capital theory and the anxiety and uncertainty theory. Data were obtained from a sample of 134 expatriate-HCN pairs who are employed in business organizations including multinational companies in the areas of Klang Valley, Malaysia. Our findings suggest that shared vision mediated significantly the influence of cultural intelligence and feedback-seeking behaviour on knowledge transfer as perceived by expatriates as well as HCNs. Implications to theory and human resource practice are discussed.